Usage of Information and Communications Technology Products and Services at Veer Surendra Sai University of Technology - Maharana, Rabindra K.; Panda, K.C. (DESIDOC Journal of Library & Information Technology, 2011)
The revolution of information technology has forced the world to depend more and more on information and communication technology products and services. Due to this rapid growth, the ICT products and services are being overwhelmingly used in all spheres of life. This paper studied the usage of different ICT products and services by the students and faculty members of Veer Surendra Sai University of Technology for fulfilling their information needs. http://dx.doi.org/10.14429/djlit.31.4.1111